A parsimonious neutral model suggests Neanderthal replacement was determined by migration and random species drift. Issue 1 (December 2017) - Kolodny, Oren; Feldman, Marcus
Abstract Most hypotheses in the heated debate about the Neanderthals' replacement by modern humans highlight the role of environmental pressures or attribute the Neanderthals' demise to competition with modern humans, who occupied the same ecological niche. The latter assume that modern humans benefited from some selective advantage over Neanderthals, which led to the their extinction. Here we show that a scenario of migration and selectively neutral species drift predicts the Neanderthals' replacement. Our model offers a parsimonious alternative to those that invoke external factors or selective advantage, and represents a null hypothesis for assessing such alternatives. For a wide range of parameters, this hypothesis cannot be rejected. Moreover, we suggest that although selection and environmental factors may or may not have played a role in the inter-species dynamics of Neanderthals and modern humans, the eventual replacement of the Neanderthals was determined by the repeated migration of modern humans from Africa into Eurasia. The replacement of Neanderthals by modern humans is thought to have been due to environmental factors, a selective advantage of modern humans, or both. Here, Kolodny and Feldman develop a neutral model of species drift showing that rapid Neanderthal replacement can be explained parsimoniously by simple migration dynamics.